1959
DOI: 10.1039/jr9590002102
|View full text |Cite
|
Sign up to set email alerts
|

424. Experiments towards the synthesis of corrins. Part III. Formation of a bicyclic oxaziran from a Δ1-pyroline and from the corresponding nitrone

Abstract: Irradiation of 5 : 5-dimethyl-Al-pyrroline 1 -oxide yields the bicyclic oxaziran (IV), also obtained by oxidation of 5 : 5-dimethylpyrroline with aqueous hydrogen peroxide. Thermal rearrangement of the oxaziran (IV) leads to 5 : 5-dimethylpyrrolid-2-oneJ whereas acidic hydrolysis yields laevulic aldehyde.Investigation of a reported 3-hydroxyoxaziran shows it to be the isomeric hydroxamic acid. RECENT investigations l s 2 have revived interest in compounds containing the threemembered carbon-nitrogen-oxygen (ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…A high energy barrier was required to form lactam through breaking of the C–CH 3 bond adjacent to the nitrogen. These results supported the experimental observations of Todd group and Lamchen group, reported almost sixty years back. The latter group carried out photo‐irradiation and pyrolysis studies on several other cyclic nitrone systems, as well.…”
Section: Introductionsupporting
confidence: 92%
“…A high energy barrier was required to form lactam through breaking of the C–CH 3 bond adjacent to the nitrogen. These results supported the experimental observations of Todd group and Lamchen group, reported almost sixty years back. The latter group carried out photo‐irradiation and pyrolysis studies on several other cyclic nitrone systems, as well.…”
Section: Introductionsupporting
confidence: 92%
“…The synthesis of nitrone 5 was first reported by Bonnett [13]. In the present work, we used a modified procedure as presented in scheme 2.…”
Section: Synthesismentioning
confidence: 99%
“…For comparison, 5,5-dimethyl-1-pyrroline-1-oxide has A, , , 234 mp (log e 3.89) in ethanol (8) and A, , , 247 mp (log E 3.94) in hexane. Ultraviolet irradiation produced a considerable decrease in absorption in all cases, presumably as a result of oxaziran formation (9). These results indicated that the base probably had structure I11 or IV, or could possibly be a mixture of the two.…”
mentioning
confidence: 56%